Science Learning Achievement Assessed from Emotional Intelligence of Students in Elementary School - Hery Kresnadi (Universitas Tanjungpura, 2019)
The purpose of this study is to describe the relationship between Emotional Intelligence and natural science learning achievement of fifth-grade students in elementary schools. The method used is descriptive qualitative. Data collection was carried out using a questionnaire to get a picture of how the emotional intelligence of fifth-grade elementary school students located in the Provincial City, Regency City, District City and remote areas, how the learning achievement of fifth-grade elementary school students in the even semester of 2019 located in the provincial city, Regency Cities, Sub-district Cities, and Remote Areas, how are the links between Emotional Intelligence and Natural Science learning achievements of Grade V students of Elementary Schools in the even semester of 2019 located in Provincial Cities, Regency Cities, District Cities, and Remote Areas. Obtained a picture there is a link between emotional intelligence with science learning achievement of fifth-grade elementary school students in the even semester of 2019 which is located in the Provincial City, Regency City, District City and Remote Areas which is stated through the results of data analysis that shows the contribution of emotional intelligence to students’ learning outcomes.